Pelatihan Menulis Esai bagi Guru-Guru AUM PCA Gatak - Sri Lestari; Gandes Nawangsari (Jumat Pendidikan: Jurnal Pengabdian Masyarakat, 2023)
One of the important skills that teachers should master to optimally develop themselves is writing. However, our data shows that teachers in AUM PCA Gatak still have poor writing skills. This community service aimed to improve the teachers’ writing skills by conducting a workshop. The invited trainer was a professional writer who is competent in writing essays. The workshop started by introducing the participants to what an essay is, its structures, and a step-by-step explanation of how to write an essay. After attending the workshop, the teachers were assigned to write an essay that should be submitted within a week after the event. The submitted manuscripts would be assessed and the best three writers would be given some appreciation. The participants were expected to have new insights and better abilities in writing.